Dwie monastyczne koncepcje – o tym co łączy a zarazem dzieli Jana Kasjana i św. Augustyna - Nehring, Przemysław (Vox Patrum, 2018)
Author of this paper juxtaposes several issues which are fundamental for monastic concepts of St. Augustine and John Cassian, two figures that had the greatest impact on the development of the western pre-Benedictine monasticism. The difference in intellectual inspirations, personal monastic experiences, addressees of their monastic works and positions held by them in the institutional Church influenced very deeply their teaching. Thus they interpret in a different manner an account on the Jerusalem community (Acts 4:31-35) that – in their common opinion – began the history of monasticism. Cassian sees in it just the historical outset for this phenomenon while Augustine perceives it as a still valid model of behavior for his monks. They look differently at the relation of monastic communities towards the community of the Church but also at inner rules governing the life of monks in monasteries. Unlike Augustine, Cassian sees possibility of spiritual growth gained by monks through ascetical practices and decisions made on their free will. This anthropological optimism had played the key-role for the statement that Cassian made in the face of radical views of Augustine on the Grace and free will, formulated by him during the Pelagian controversy but also in other controversial issue, namely of possible legitimacy of lying under particular circumstances.